CLT from recycled wood: Fabrication, influence of glue pressure and lamina quality on structural performance. (16th May 2023) - Carrasco, E.V.M.; Pizzol, V.D.; Smits, M.A.; Alves, R.C.; Oliveira, A.L.C.; Mantilla, J.N.R.
Highlights: It is possible to reuse discarded sleepers in the manufacture of CLT panels. NDT is an efficient tool for classifying and identifying defects in laminas obtained from sleepers. The bonding pressure that provided the best bond strength was 1.5 MPa. The modulus of elasticity in the 3L direction is 122% higher than in the 2L direction. Abstract: This work aims to present the manufacture of cross-laminated timber (CLT) with recycled wood from discarded sleepers. In order to obtain a high-performance CLT, the influence of the gluing pressure on the shear strength of the glue line was studied, as well as the quality of the recycled boards made through a visual classification, with ultrasound and three-point bending tests. To prove the efficiency of the CLT, the modulus of elasticity was determined using strain gauges. It was concluded: it is possible to reuse discarded sleepers for making CLT, ultrasound is an efficient tool for mechanical classification of the laminas and the gluing pressure that provided the best resistance for the glue line was 1.5 MPa.